E-Commerce Tax: From e-Filing to Coretax (A Bibliometric Analysis) - Michael Michael (Politeknik Ganesha Medan, 2026)
This study aims to map the development of research related to digital taxation in the context of e-commerce through a bibliometric approach and a systematic analysis of the literature, encompassing 538 articles identified from the Crossref database for the period 2010–2025. The results of the study indicate that the research theme has shifted from administrative and legal issues to the dimension of taxpayer behaviour and the adoption of digital tax technologies, such as e-filing and the Coretax Administration System. The analysis using VOSviewer identified three main clusters: administrative technology, behavioural compliance, and policy governance, with dominant keywords including tax compliance, trust, digitalisation, and e-commerce VAT. The integration between the Theory of Planned Behaviour (TPB) and the Technology Acceptance Model (TAM) was identified as a relevant theoretical foundation for explaining digital tax compliance behaviour in the modern era. Practically, the results of this study provide implications for tax authorities and e-commerce industry players to increase trust, transparency, and digital literacy in the implementation of an integrated tax system. This research contributes to enriching the literature on digital taxation in developing countries and recommends further empirical testing of the conceptual model of the Digital Tax Compliance Framework for E-Commerce in Indonesia, aiming to strengthen data-driven tax governance in the digital economy era.